Pomen dominantnosti okončin na porazdelitev pritiska po otroškem stopalu - Dominik Kocbek; Miha Marinšek (Journal of Elementary Education, 2012)
The Importance of Limb Dominance for Foot Pressure Distribution in Children. The aim of our study was to test how lateral preference, visual deprivation, and different foot placements affected postural stability of five-year-olds. We studied nineteen children aged 5.3 ± 0.2, of which 9 boys and 10 girls. Six were leftfooted. Four foot positions (feet together, feet apart, tandem, step) and two visual conditions (eyes open, eyes closed) were tested during a 60-second quiet stance. Lateral preference was considered. We used Parotec foot insoles to measure various centre of pressure variables. The data was exported to an Excel spreadsheet file where chosen variables were calculated. The differences in foot positions and visual conditions were identified through variance analysis, while the differences between dominant and non-dominant foot were tested with the use of paired t-test. The results showed that children on average load their non-dominant foot more than their dominant one. The dominant foot utilized more corrections to enable stability of the body than the non-dominant foot, which can be seen from the longer path of the centre of pressure of the dominant foot in comparison to the non-dominant foot. In most of the cases, children used their non-dominant foot to bear the weight and their dominant foot for postural control during quiet stance. We also discovered that the reduction of the base of support in the lateral direction significantly decreased children's stability.